Wisdom from the Edge : Writing Ethnography in Turbulent Times - Stoller, Paul (Book collections on Project MUSE., 2023)
"This book presents a blueprint for doing anthropology in troubled times. It instructs readers on how to convey important anthropological insights-indigenous wisdom-to a general audience in search of solutions to cotemporary social problems."--